Further investigation of the interaction of prosodic elements in the Baltic languages: a perception-based analysis of Latvian lexical tones - Švageris, Evaldas (Baltistica, 2021)
This article presents recent attempts to clarify the nature of phonetic interaction between two prosodic elements, namely between the intonation and contour tones. A perception test was conducted for this purpose. The main focus was on the perception of Standard Latvian contour tones produced under different intonational conditions. The results of the study can be considered as empirical basis for the verification of a three-parameter research model that has recently been applied in some experimental investigations of Baltic prosody. The clear separation of data in 3D scatter plots revealed important perception-based evidence in favour of this model. In particular, the contour tones clearly determine the type of interaction (function mathematically) between duration, F0 acceleration, and F0 jerk. Furthermore, it is possible to draw boundaries in acoustic space between elements of different prosodic status, i.e., to indicate their positions in relation to each other. All these facts support the assumption that prosodic elements are best understood and defined in terms of duration-pitch interaction. In other words, they are key factors that differentiate pitch dynamics (the amount and distribution of voice energy in a wider sense) in relation to time.